Joy and Responsibility: Weaving the Hopes of Street-Selling Children in Dili, Timor-Leste - Alise de Fatima Noronha (The Indonesian Institute of Science and Technology Research, 2025)
This study explores the lives of street-selling children in Dili, Timor-Leste, who support their families through informal economic activities. Using a qualitative library-based research approach, the study highlights their dual roles as sources of family income and children with dreams and emotional needs. These children often work under harsh conditions and face social stigma. Only 40% of them have access to formal education. Despite this, they express strong educational aspirations, better livelihoods, and social recognition. The article emphasizes the urgency of inclusive educational policies, child protection laws, and government and civil society collaborative efforts to ensure a supportive environment for these vulnerable children. This research contributes to understanding the intersection of child labor, education access, and child welfare in post-conflict developing countries.